Significance of Immunohistochemical Expression of Survivin in Renal Cell Carcinoma - Mohammed, Maisa Hashem; Abd El-Sadek Ahmed, Nagwa (Asian Pacific Journal of Cancer Biology, 2021)
Background: Evasion of apoptosis is an essential alteration for cellular genetic mutation. Survivin is a member of inhibitor of apoptosis protein (IAP) family. Under normal conditions, Survivin is expressed in embryonic and fetal tissues and markedly diminished in mature, differentiated adult tissues. Survivin was found to be re-expressed in multiple solid and hematological human malignant neoplasms. The purpose of this study was to evaluate the expression of Survivin in renal cell carcinoma (RCC), and to find statistically significant associations between Survivin and the tested Clinicopathological parameters. Methods: 39 patients with RCCs who underwent nephrectomy were included in the study. From each RCC specimen, two tissue sections were obtained; one was stained by H&E stain to determine both RCC phenotype and Fuhrman’s nuclear grades. The second tissue section was immunohistochemically stained by anti-human Survivin antibody. Results: The study revealed statistically significant associations between Survivin expression in RCC specimens and RCC histological types (p =0.002), high tumor grade (p< 0.001) and advanced tumor stage (p< 0.001). Conclusion: The study revealed that Survivin is positively correlated to poorly differentiated RCCs with high Fuhrman’s nuclear grade and advanced tumor stage.